Diabetes Practice Update: Diabetic Peripheral Neuropathy, Retinopathy, and Chronic Kidney Disease - Shuman, Jill (MD Conference Express, 2014)
This article discusses new insights on the diabetic eye, assessing and managing ocular complications of diabetes, as well as diabetic kidney disease.